P‐111: Healthy Light Sources for Lighting and Displays. Issue 1 (May 2016) - Jou, Jwo-Huei; Tsai, Yi-Fang; Su, Yu-Ting; He, Zhe-Kai
Abstract : Over exposure to lights may cause retina damage day and night, and suppress melatonin secretion at night. We have developed an action spectrum to quantify the potential threat of ambient lights on melatonin generation. We will also present a universal curve depicting how the color temperature and illuminance of a given light determine the permissive exposure‐limit. With these, healthy lights can hence be designed and proper lighting measures or levels be selected, accordingly.